2008
DOI: 10.1534/genetics.108.091355
|View full text |Cite
|
Sign up to set email alerts
|

Diploid/Polyploid Syntenic Shuttle Mapping and Haplotype-Specific Chromosome Walking Toward a Rust Resistance Gene (Bru1) in Highly Polyploid Sugarcane (2n ∼ 12x ∼ 115)

Abstract: The genome of modern sugarcane cultivars is highly polyploid (12x), aneuploid, of interspecific origin, and contains 10 Gb of DNA. Its size and complexity represent a major challenge for the isolation of agronomically important genes. Here we report on the first attempt to isolate a gene from sugarcane by map-based cloning, targeting a durable major rust resistance gene (Bru1). We describe the genomic strategies that we have developed to overcome constraints associated with high polyploidy in the successive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 46 publications
(62 reference statements)
0
98
0
7
Order By: Relevance
“…Therefore, the release of cultivars that are resistant to brown rust is very important and is the most efficient form of disease control. The genetic inheritance of brown rust in sugarcane has been broadly studied, and some researchers have claimed that this resistance trait is controlled by one or a few genes (Asnaghi et al, 2004;Costet et al, 2012;Daugrois et al, 1996;Garsmeur et al, 2011;Glynn et al, 2013;Hogarth et al, 1993;Le Cunff et al, 2008;Parco et al, 2014;Raboin et al, 2006;Racedo et al, 2013;Ramdoyal et al, 2000;Sordi et al, 1988). In contrast to that shown for brown rust, almost every trait that is related to sugarcane production exhibits quantitative variations.…”
Section: Mixed Modeling Of Yield Components and Brown Rust Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the release of cultivars that are resistant to brown rust is very important and is the most efficient form of disease control. The genetic inheritance of brown rust in sugarcane has been broadly studied, and some researchers have claimed that this resistance trait is controlled by one or a few genes (Asnaghi et al, 2004;Costet et al, 2012;Daugrois et al, 1996;Garsmeur et al, 2011;Glynn et al, 2013;Hogarth et al, 1993;Le Cunff et al, 2008;Parco et al, 2014;Raboin et al, 2006;Racedo et al, 2013;Ramdoyal et al, 2000;Sordi et al, 1988). In contrast to that shown for brown rust, almost every trait that is related to sugarcane production exhibits quantitative variations.…”
Section: Mixed Modeling Of Yield Components and Brown Rust Resistancementioning
confidence: 99%
“…The severity of brown rust is assessed on a particular scale (Amorim et al, 1987;Tai et al, 1981), and the frequency of full-sib genotypes in each severity class is influenced by the genetic basis of the parents of the family. Several researchers have reported that brown rust resistance is controlled by one or a few genes (Asnaghi et al, 2004;Costet et al, 2012;Daugrois et al, 1996;Garsmeur et al, 2011;Glynn et al, 2013;Hogarth et al, 1993;Le Cunff et al, 2008;Parco et al, 2014;Raboin et al, 2006;Racedo et al, 2013;Ramdoyal et al, 2000;Sordi et al, 1988). Costet et al (2012) showed that resistance to brown rust in modern polyploid sugarcane cultivars essentially depends on the major gene Bru1.…”
Section: Probabilities Segregations and Heritability Of Resistance mentioning
confidence: 99%
“…Therefore, the opportunity exists to utilize Bru1 in marker-assisted breeding and selection in order to improve brown rust resistance in sugarcane [29]. Bru1 has been used as a marker to identify if sugarcane genotypes are potentially resistant to brown rust [25,30,31]. Since 2009, this marker has also been utilized in the CP program to direct breeding strategies for brown rust resistance [29].…”
Section: Bru1 In Parental Clones and Rust Rating In Their Progenymentioning
confidence: 99%
“…A base da herança genética de resistência a essa doença tem sido amplamente estudada e alguns autores defendem que a resistência é controlada por um ou poucos genes (18,25,26,27,28,29,30,31,32,33). Um gene de resistência, denominado Bru1, foi o primeiro caráter mendeliano descrito para o complexo genoma da cana-de-açúcar (18,26,30,32).…”
Section: Introductionunclassified
“…Estudos genômicos têm mostrado que Bru1 está incluído numa inserção de tamanho desconhecido (31,34). Esta inserção induz redução de recombinação, resultando em forte desequilíbrio de ligação (LD) na região Bru1 e um completo LD entre dois marcadores moleculares, R12H16 e 9O20-F4.…”
Section: Introductionunclassified